Towards a more systematic approach to the development of terminology in Sepedi - Letsoalo, Napjadi Eugene (My University, 2015)
Refer to the document
Thesis (M. (Translation Studies and Linguistics)) -- University of Limpopo, 2015
Keywords: African linguistic; Systematic approach; Sotho language; Terminology in Sepedi; Linguistics; Northern Sotho language -- Grammar -- Terminology; Terminology; Language and languages